Different sources of capitalism's instability: Finance in Minsky and money in The General Theory - Elisabetta De Antoni (Intervention. European Journal of Economics and Economic Policies, 2010)
First paragraph: Hyman P. Minsky (1975; 1982a and 1986) presented his »financial instability hypothesis« (FIH) as a cyclical interpretation of The General Theory (TGT) which highlighted Keynes's most innovative insights. This paper compares Minsky's FIH with the 22nd Chapter of TGT, which Keynes expressly devoted to the business cycle. From this perspective, the next two sections will bring to light the different subjects of the analyses and the disparate conceptions of the business cycle. Lastly, the last section will focus on the different roles assigned to money and finance and on their concrete relevance.
Keywords: 330